POLYMERS IN MEDICINE FROM DRUG DELIVERY TO BIOMATERIALS (The Research of Medical Science Review, 2025)
Polymers have revolutionized the field of medicine, offering innovative solutions in drug delivery and biomaterials. Their versatility, tunable properties, and biocompatibility make them ideal candidates for various biomedical applications. In drug delivery, polymeric systems such as nanoparticles, micelles, hydrogels, and dendrimers enable controlled, targeted, and stimuli-responsive drug release, improving therapeutic efficiency and reducing side effects. Biodegradable and synthetic polymers like PLGA, PEG, and chitosan have been extensively explored for enhanced drug stability and bioavailability. Beyond drug delivery, polymers play a crucial role in biomaterials, including tissue engineering, wound healing, and medical implants. Natural polymers like collagen and alginate, alongside synthetic materials such as PEEK and PMMA, offer structural support and functional enhancements for biomedical applications. The advent of smart polymers, including pH-responsive and temperature-sensitive materials, has further advanced regenerative medicine, biodegradable implants, and biosensors. Despite their advantages, challenges such as mechanical stability, long-term biocompatibility, and regulatory approval remain. Recent advancements, including 3D printing of polymeric medical devices and bioactive polymer development, continue to push the boundaries of medical technology. This review explores the critical role of polymers in medicine, highlighting their applications in drug delivery and biomaterials, addressing current challenges, and discussing prospects in personalized medicine and smart healthcare solutions.